One-step photostructuring of multiple hydrogel arrays for compartmentalized enzyme reactions in microfluidic devices. Issue 12 (30th October 2019) - Obst, Franziska; Simon, David; Mehner, Philipp J.; Neubauer, Jens W.; Beck, Anthony; Stroyuk, Oleksandr; Richter, Andreas; Voit, Brigitte; Appelhans, Dietmar
Abstract : A moulding technique is presented for the simultaneous photostructuring on the μm scale of hydrogels with nanomaterials on one substrate, usable for the fabrication of microfluidic double-chamber reactors. Abstract : We present a technique for the simultaneous photostructuring of hydrogels on the μm scale with different compositions on one substrate. The existing methods ( e.g. spin-coating of the hydrogel precursor and application of simple moulds or spacers) have less potential to integrate spatially separated functional hydrogel dots as needed for the fabrication of complex polydimethylsiloxane (PDMS) on-glass microfluidic chips. Here, we report a method for the fast production of precisely placed hydrogel structures with adjustable height (≤80 μm) and width (≤500 μm) on glass substrates utilizing black polyoxymethylene moulds. The integration of several chambers for different hydrogel precursor solutions in one mould allows the simultaneous photopolymerization of hydrogels with different compositions. To visualize the difference in composition of the hydrogel dots and to demonstrate the precision in structuring, various quantum dots were added to the hydrogel precursor solutions and physically entrapped during the photopolymerization. To show the high potential of our photostructuring method, a microfluidic double-chamber reactor was designed and the variability in the performance of tri-enzymatic cascade reactions with optionally spatially separated or non-separated enzymes β-galactosidase, glucose oxidase, and horseradish peroxidase was visualized.